How to prevent a RC frame structure collapsing in a strong earthquake - Zhao, Zuozhou (2021)
Based on seismic design code of China GB50011, RCframesaredesigned based on ductility frame requirements. ① Seismic design objective(3 levels): Elastic under Service level EQ (SLE) (Pf=63.2%) Repairable under Design basis EQ(DBE) (Pf=10%) Non-collapse under MaximumconsideredEQ(MCE)(Pf=2%